GIVING INCENTIVES TO INCREASE MOTIVATION AND EMPLOYEE WORK PERFORMANCE AT NOVOTEL NGURAH RAI AIRPORT - Gus Manik Eka Adnyana; I Ketut Suparta; I Gusti Made Wendri (Journal of Applied Sciences in Travel and Hospitality, 2018)
Motivation and Employee work performance is the thing that need to be noticed by all companies in order to achieve maximum results in carrying out the duties and responsibilities that have been given. Incentives are a form of company rewards to employees for the achievements that have been achieved and have performed duties and responsibilities well, so as to motivate employees in the work. The purpose of this paper is to find out how the terms and criteria of giving incentives to employees at Novotel Ngurah Rai Airport Kuta Bali and to find out whether incentives can improve employee motivation and work performance at Novotel Ngurah Rai Airport Kuta Bali. Analytical tool used is qualitative analysis and using qualitative data. The result of the research shows that incentives can improve employee motivation and performance based on the terms and criteria of giving incentives to employees.